LBA2TATTON expansion cohorts: A phase Ib study of osimertinib plus savolitinib in patients (pts) with EGFR-mutant, MET-positive NSCLC following disease progression on a prior EGFR-TKI. (24th November 2019) - Han, J-Y; Sequist, L V; Ahn, M-J; Cho, B C; Yu, H; Kim, S-W; Yang, J C-H; Lee, J S; Su, W-C; Kowalski, D; Orlov, S; Cantarini, M; et al.
Abstract: Background: Preliminary data from TATTON (NCT02143466, a multi-arm, multi-drug combination study) suggested that adding savolitinib (AZD6094, HMPL-504, volitinib), a potent and highly selective MET TKI, to osimertinib, a 3 rd generation, irreversible epidermal growth factor receptor tyrosine kinase inhibitor (EGFR TKI), which selectively inhibits EGFR TKI sensitising (EGFRm) and T790M resistance mutations, may overcome MET-driven resistance to EGFR TKIs. We present updated data from TATTON Part B and data from Part D, for the first time. Methods: Pts were ≥18 years (Japan ≥20 years), mainly Asian, with locally advanced/metastatic, MET-positive, EGFRm NSCLC and disease progression on prior therapy. Pts enrolled based on MET status by local fluorescent in-situ hybridisation (MET gene copy ≥5 or MET/CEP7 ratio ≥2), next-generation sequencing or immunohistochemistry (+3 in ≥ 50% of tumour cells), with retrospective central confirmation. Pts in Part B received osimertinib 80 mg + savolitinib 600 mg or 300 mg orally (PO) once daily (QD). Pts in Part D received osimertinib 80 mg + savolitinib 300 mg PO QD, were T790M negative and had received no prior 3 rd generation EGFR TKI. Primary endpoints: safety and tolerability; secondary endpoints included objective response rate and progression-free survival. Results: In Parts B (N = 138) and D (N = 42); Grade ≥3 AEs reported by 57% and 38%, respectively; serious AEs reported by 45% and 26%, respectively. AEs possibly related to treatment, led to discontinuation of savolitinib in 38 (28%) vs 9 (21%) and osimertinib in 14 (10%) vs 2 (5%), for Parts B and D, respectively. Efficacy data: Table. Conclusions: Our results support that osimertinib + savolitinib may overcome MET-driven resistance to EGFR TKIs, and warrant further exploration of the osimertinib 80 mg + savolitinib 300 mg combination in the SAVANNAH (NCT03778229) and ORCHARD (NCT03944772) studies. Clinical trial identification: NCT02143466. Editorial acknowledgement: Laura Crocker, BMedSci, of iMed Comms, an Ashfield Company, funded by AstraZeneca. Legal entity responsible for the study: AstraZeneca. Funding: AstraZeneca. Disclosure: J. Han: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: BMS; Advisory / Consultancy: Lilly; Honoraria (self), Advisory / Consultancy: MSD; Advisory / Consultancy: Novartis; Research grant / Funding (self): ONO; Advisory / Consultancy, Research grant / Funding (self): Pfizer; Honoraria (self), Research grant / Funding (self): Roche; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): Takeda. L.V. Sequist: Honoraria (self), Research grant / Funding (institution): AstraZeneca; Honoraria (self): Janssen; Research grant / Funding (institution): Novartis; Honoraria (self), Research grant / Funding (institution): Merrimack Pharmaceuticals; Research grant / Funding (institution): Boehringer Ingelheim; Research grant / Funding (institution): LOXO; Honoraria (self), Research grant / Funding (institution): Blueprint Medicines; Honoraria (self), Research grant / Funding (institution): Genentech. M. Ahn: Honoraria (self), Advisory / Consultancy: AstraZeneca, Bristol-Myers Squibb, MSD, Ono Pharmaceutical, Roche; Advisory / Consultancy: Takeda, Alpha Pharmaceutical. B.C. Cho: Research grant / Funding (institution): Novartis, Bayer, AstraZeneca, Mogam Institute, Dong-A ST, Champions Oncology, Janssen, Yuhan, Ono Pharmaceutical, Dizal Pharma, MSD; Advisory / Consultancy: Novartis, AstraZeneca, Boehringer Ingelheim, Roche, Bristol-Myers Squibb, Ono Pharmaceutical, Yuhan, Pfizer, Eli Lilly, Janssen, Takeda, and MSD; Shareholder / Stockholder / Stock options: TheraCanVac Inc, Gencurix Inc, Bridgebio Therapeutics; Licensing / Royalties, Patent with royalties paid: Champions Oncology. H. Yu: Advisory / Consultancy: AstraZeneca; Research grant / Funding (institution): AstraZeneca, Lilly, Pfizer, Daiichi, Novartis, Astellas. S. Kim: Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca. J.C. Yang: Honoraria (self): AstraZeneca, Boehringer Ingelheim, Eli Lilly, Bayer, Roche/Genentech, Chugai, MSD, Pfizer, Novartis, Bristol-Myers Squibb, Ono Pharmaceuticals; Advisory / Consultancy: AstraZeneca, Boehringer Ingelheim, Eli Lilly, Bayer, Roche/Genentech, Chugai, Astellas, MSD, Merck Serono, Pfizer, Novartis, Celgene, Merrimack, Yuhan Pharmaceuticals, Bristol-Myers Squibb, Ono Pharmaceuticals, Daiichi Sankyo, Hansoh, Takeda, Blueprint. M. Cantarini: Shareholder / Stockholder / Stock options, Full / Part-time employment, Full time Contractor: AstraZeneca. R.B. Verheijen: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca; Shareholder / Stockholder / Stock options: Aduro Biotech. A. Mellemgaard: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. P. Frewer: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. X. Ou: Full / Part-time employment, Full time Contractor: AstraZeneca. G. Oxnard: Honoraria (self): Chugai Pharma, Bio-Rad, Sysmex, Guardant Health, Foundation Medicine; Advisory / Consultancy: AstraZeneca, Inviata, Takeda, Loxo, Ignyta, DropWorks, GRAIL, Illumina, Janssen; Licensing / Royalties, Patent pending: DFCI.